The sustainability of Latin American CSOs: historical patterns and new funding sources. Issue 5 (3rd July 2016) - Pousadela, Inés M.; Cruz, Anabel
ABSTRACT: As an increasingly consolidated middle-income region, Latin America's position within the international aid architecture has shifted. Funding for civil society has decreased as a result of economic growth, crises affecting bilateral donors, and operational and financial restrictions stemming from political polarisation and increasing government hostility in various countries. Based on a current and historical literature review as well as informal consultations with CSO sources, this article summarises the results of a research project focused on civil society's funding mechanisms in Latin America and accounts for recent CSO efforts to explore novel funding alternatives.